Increased elbow and olecranon injury history in professional pitchers with increased elbow flexion at ball release - Manzi, J. E.; Cicotti, M. C.; Trauger, N.; Black, G. G.; Thacher, R. R.; Boddapati, V.; Dines, J. S. (The American Journal of Sports Medicine, 2022)
Background: Elbow flexion at late portions of the pitch has been associated with increased elbow varus torque, a kinetic surrogate associated with injury risk. Direct examinations of injury incidence with elbow flexion angles have not been conducted in professional pitchers.